Muscle perfusion and the effect of compression garments in delayed-onset muscle soreness assessed with arterial spin labeling magnetic resonance imaging - Meixner, Christian; Nagel, Armin Michael; Höger, Svenja; Gast, Lena; Wiesmüller, Marco; Uder, Michael; May, Matthias; Hotfiel, Thilo; Heiß, Rafael (Quantitative Imaging in Medicine and Surgery, 2022)
Background: There is limited information about perfusion in exercise-induced muscle injuries such as delayed-onset muscle soreness (DOMS) and the effect of compression garments as a therapeutic strategy during the regeneration phase. The purpose of this prospective, explorative study was to evaluate muscle perfusion in DOMS and to assess the effect of compression garments at resting conditions and during DOMS by magnetic resonance (MR) arterial spin labeling (ASL). Methods: DOMS was induced from 03/2021 to 04/2021 using an eccentric and plyometric exercises targeting the calf muscles in 14 volunteers. A compression garment (21-22 mmHg) was worn during and for 6 h after exercise on one randomized leg. Magnetic resonance imaging (MRI) including ASL of both lower legs was performed before and directly after the exercise as well as after 6 h, and 48 h using a 3 Tesla MRI system. Perfusion analyses of the gastrocnemius muscle (GM) and the tibialis anterior muscle (TA) were performed and results were compared to baseline measurements. T2-weighted images and creatine kinase levels were acquired at baseline and after 48 h. Results: All volunteers presented a successful induction of DOMS in the GM after 48 h. Arterial muscle perfusion in the GM increased from baseline to measurements taken directly after the exercise (4.97 +/- 5.59 mL/100 g/min, P<0.001). No significant alteration in perfusion compared to baseline was observed at 6 h (P=0.16) and 48 h (P=1.0) after the induction of DOMS. Compression garments did not elicit a significant alteration in ASL parameters in the GM (P=0.65) or the TA (P=0.05) at any time point. No adverse events occurred during the study. Conclusions: After an initial exercise-associated increase in arterial muscle perfusion, a normalization of blood supply was observed at 6 and 48 h after the exercise intervention inducing DOMS. Wearing a compression garment (21-22 mmHg) during and after the induction of DOMS did not affect muscle perfusion at rest, nor did it have any significant effect on muscle perfusion during the regeneration phase. The results can help to better understand the pathophysiological properties of DOMS and may have implications for diagnostic and therapeutic strategies.
CRIS-Team WoS Importer:2022-08-05